Simulating cement hydration using HYDCEM. (10th April 2020) - Holmes, Niall; Kelliher, Denis; Tyrer, Mark
Highlights: A new cement hydration model simulating volumetric changes and phase assemblages. Simulations of the volumetric growth of hydration products in PC and limestone cements. Complements thermodynamic models with reasonable predictions over time. Incorporates up to date cement hydration behaviour from the literature. Easy to use with changeable inputs of cement chemistry and physical properties. Abstract: HYDCEM is a new cement hydration model to simulate volumetric changes and predict phase assemblage, degree of hydration, heat release, compressive strength and chemical shrinkage over time for PC and limestone binders undergoing hydration for any w/c ratio and curing temperatures between 5 and 45 °C. While models should never completely remove experimental analysis, they are an aid to better understand cement hydration and microstructure development by allowing users analyse different binders in a relatively short time. HYDCEM, written in MATLAB®, is aimed at complementing more sophisticated thermodynamic models giving users a reasonable prediction of hydration behaviour over time, using user-customisable inputs. A number of functions based on up to date cement hydration behaviour from the literature are included along with user-changeable inputs such as the cement chemical (oxide) composition, cement phase densities, species molar mass, phase and product densities and heat of hydration enthalpies. HYDCEM uses this input to predict the cement phase and gypsum proportions, volume stoichiometries and growth of hydration products including C-S-H, calcium hydroxide, hydrogarnet (if applicable), hydrotalcite, ettringite, monosulphate, hemicarbonate and monocarbonate if limestone is present. A number of comparisons with published experimental and thermodynamic model results and HYDCEM predictions are provided to demonstrate its accuracy and usefulness. Previous work has shown that HYDCEM can reasonably accurately predict phase assemblages in terms of volume change and behaviour for a range of cements and curing temperatures.